2010
DOI: 10.1017/s1751731110000261
|View full text |Cite
|
Sign up to set email alerts
|

Transport of cations and anions across forestomach epithelia: conclusions from in vitro studies

Abstract: Secretion of saliva as well as absorptive and secretory processes across forestomach epithelia ensures an optimal environment for microbial digestion in the forestomachs. Daily salivary secretion of sodium (Na 1 ) exceeds the amount found in plasma by a factor of 2 to 3, while the secretion of bicarbonate (HCO 3 2 ) is 6 to 8 times higher than the amount of HCO 3 2 in the total extracellular space. This implies a need for efficient absorptive mechanisms across forestomach epithelia to allow for an early recycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 148 publications
1
35
0
Order By: Relevance
“…For the rumen epithelium, we could show recently the existence of a nonspecific cation conductance which might contribute to the absorption of Ca across the rumen wall (Leonhard‐Marek ; Leonhard‐Marek et al. , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the rumen epithelium, we could show recently the existence of a nonspecific cation conductance which might contribute to the absorption of Ca across the rumen wall (Leonhard‐Marek ; Leonhard‐Marek et al. , ).…”
Section: Discussionmentioning
confidence: 99%
“…Using the everted gut sac assay, no differences in duodenal active Ca transport could be detected between wild-type, TRPV6 knockout, CaBP 9K knockout, and TRPV6/CaBP 9K double knockout mice fed a standard rodent chow diet (Benn et al 2008). For the rumen epithelium, we could show recently the existence of a nonspecific cation conductance which might contribute to the absorption of Ca across the rumen wall (Leonhard-Marek 2002;Leonhard-Marek et al 2005, 2010.…”
Section: Structural Equivalents Of Ca Transportmentioning
confidence: 99%
“…Ruminal short-chain FA (SCFA) can be efficiently absorbed by the rumen epithelium via diffusion or a protein-mediated pathway (Leonhard-Marek et al, 2010;Aschenbach et al, 2011). Past research has demonstrated that feeding a high-concentrate diet could lead to enhanced SCFA absorptive capacity of rumen epithelium (Gäbel et al, 1991), even when no change occurred in the absorptive surface area of the rumen papillae (Sehested et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…, Leonhard‐Marek et al . ). However, the quantitative contributions and identities of these transport proteins are still under discussion.…”
mentioning
confidence: 97%
“…() and Leonhard‐Marek et al . () assumed a solely electrogenic transfer via an anion channel, Connor et al . () and Kirat et al .…”
mentioning
confidence: 99%